Careful Where You Cut: Strategies for Successful Nerve-preserving Mastectomy - Suzanne Coopey, MD; Angela Keleher, MD; Karla Daniele, MD; Anne Warren Peled, MD; Janette Gomez, DO; Thomas Julian, MD; Andrea A. Moreira, MD, FACS (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Breast neurotization represents an evolving technique that is not widely practiced in most centers specializing in breast cancer treatment. Recognizing the limited educational resources available for breast and plastic surgeons concerning mastectomy techniques that emphasize nerve preservation, our study sought to bridge this gap. Specifically, we aimed to provide a comprehensive exploration of the surgical applied anatomy of breast sensory innervation and a detailed, step-by-step guide for incorporating nerve-sparing mastectomy and breast neurotization into clinical practice. The significance of this work lies in its potential to enhance the understanding and implementation of nerve-preserving techniques in mastectomy procedures, contributing to improved patient outcomes and quality of life post surgery. We hope that by familiarizing breast and reconstructive surgeons with this procedure, we can gain momentum in our research efforts and ultimately enhance the care provided to mastectomy patients.